Decision Analysis To Rent of Co-Working Space and Virtual Office in Jabodetabek Areas - Lisdiawati, Hartika; Sumarwan, Ujang; Yuliati, Lilik Noor (Indonesian Journal of Business and Entrepreneurship, 2024)
Technology and the new normal make the working model more flexible. Co-working space is also present in line with these changes. Customer awareness is in good results but the fact is not in line with existing business practices. Several co-working spaces experienced decreased visits, unstable sales, and received losses. The purpose of this study is to analyze the factors that influence the decision to rent from the variables mediating perceived benefits and costs with the influencing variables being customer motivation, reliability, reputation, and convenience. The sample collected was 259 respondents who were consumers who had rented a co-working space located in Jabodetabek which was the scope of the study as well. In a multivariate analysis with SEM-PLS, the research results of the decision to rent were significantly more influenced by perceived benefits than costs. The biggest benefit is influenced by customer motivation and the cost is influenced by reliability. The new results of this study show that the reputation variable is consistently not significant in rent decisions. Keywords: coworking space, decision to rent, perceived benefit, perceived cost, SEM-PLS